Experiences related to contraception by HIV-infected women that become pregnant - Romanelli, Roberta MC; Cardoso, Carolina S; Lin, Elisa MR; Goulart, Lúcia HF; Aguiar, Regina Amélia LP; Pinto, Jorge A (Brazilian Journal of Sexually Transmitted Diseases, 2007)
Introduction: an increasing number of HIV infected women has being identified, mainly at reproductive age. Although they receive all measures toprevention of vertical transition, difficulties in postnatal assistance has being observed, including occurrence of unplanned pregnancies. Objective: toinvestigate perceptions about contraceptive methods of a new pregnancy by women that already new they were HIV-infected and that had childrenpreviously. Methods:this is a clinical-qualitative study, developed at outpatient service Carlos Chagas of Clinics Hospital of Federal University ofMinas Gerais, from January 2004 until December 2005. Women that knew their serologic status and that already had other children were included.The number of interviews was defined by saturation criteria. Semi-structured interviews were performed and then recorded and transcribed entirely.Data were analyzed according to categorization process. Results:twenty women were interviewed, with median age of 29 years. Women medianpregnancies was 3,5, but after diagnosis was 1,04. Nineteen pregnancies were not planed. Women showed information about contraceptive methods,but reported their difficulties in the use of condom by their partner, difficulties to use oral contraceptives and access to salpingotripsy. Conclusion:occurrence of a new pregnancy was not depended on knowledge of HIV infection. Expectations and desires can be modified by disease stigma butwere not determinants to use a effective contraceptive method. Healthy professionals should focus on complete assistance to these women, facilita-ting utilization of contraception in order that their reproductive rights are achieved.